Pengembangan Kapasitas UMKM Kelurahan Padangsari dalam Pembuatan Konten Visual untuk Meningkatkan Branding dan Daya Saing - Nurul Juwariyah; Nur Hasanah; Titi Purbo Sari; Hendra Wijaya (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
This community service program aims to enhance the capacity of UMKM Mentari Padangsari in developing visual content to strengthen branding and competitiveness. It is hoped that this training activity will have an impact on the development of MSMEs in Padangsari sub-district.The main problems faced by partners include limited skills in creating product photos, graphic designs, promotional videos, and managing social media consistently. The program was implemented through training, mentoring, and evaluation stages involving 14 UMKM actors in Padangsari Village, Semarang City. Training materials focused on product photography using smartphones, simple graphic design, short promotional videos, visual storytelling, and the use of digital platforms such as social media and Google Business are  considered very necessary in this era of rapid technological development. The results show increased knowledge and skills among UMKM actors in producing more attractive visual content, improving brand identity, and enhancing engagement on social media. This program contributes to strengthening UMKM competitiveness and supports sustainable digital-based marketing practices.